Transforming Academic Literacy: Centering Indigenous Identities in the Classroom - Oscar Eybers (Genealogy)
This article explores the transformational potential of centering indigenous identities and heritage within academic literacy instruction in higher education. The dominance of Eurocentric pedagogies in higher education has often marginalized African epistemologies and cultural narratives, limiting students’ engagement and sense of belonging. Drawing on examples such as the Ma’at and Tewahedo traditions, this work argues that academic literacy should embrace Indigenous Knowledge Systems and the cultural capital students bring to the classroom. By integrating indigenous identities into disciplinary discourses, educators can create more inclusive learning environments that challenge historical power dynamics and elevate marginalized voices. This analysis highlights practical strategies for educators to foster critical thinking, reading, and writing while affirming students’ identities. Ultimately, this article demonstrates that activating Indigenous Knowledge Systems can create classrooms that are inclusive and reflective of African identities.